IDENTITY, PERSPECTIVES AND INTERPRETATIONS OF CHILD LABOR IN BRAZIL - Wenczenovicz, Thais Janaina; Siqueira, Rodrigo Espiúca dos Anjos (Unoesc International Legal Seminar, 2017)
Studies that emphasize the importance of the evolution of human rights in Western countries and their deployment in Brazil must include the exploitation of child labor. This is a recurring theme in academic and socio-political discussions, over the centuries, through its facets and dimensions in today's society. This article aims to analyze child labor in Brazil. Therefore, in its first part, it traces elements about childhood and the world of work, followed by a brief historical review of child labor. It also brings some aspects of national and international law evidencing the rules pertaining to the topic.